Trends in Adult and Elderly Vaccination: Focus on Vaccination Practices in Tunisia and Morocco - Redouane Abouqal; Redouane Abouqal; Maher Beji; Maher Beji; Maher Beji; Mohamed Chakroun; Kamal Marhoum El Filali; Jihane Rammaoui; Hela Zaghden (Frontiers Media S.A., 2022)
Vaccine preventable diseases (VPDs) are a prevailing concern among the adult population, despite availability of vaccines. Unlike pediatric vaccination programs, adult vaccination programs lack the required reach, initiative, and awareness. Clinical studies and real-world data have proven that vaccines effectively reduce the disease burden of VPDs and increase life expectancy. In Tunisia and Morocco, the national immunization program (NIP) focuses more on pediatric vaccination and have limited vaccination programs for adults. However, some vaccination campaigns targeting adults are organized. For example, influenza vaccination campaigns prioritizing at risk adults which includes healthcare professionals, elderly, and patients with comorbidities. Women of childbearing age who have never been vaccinated or whose information is uncertain are recommended to receive tetanus vaccination. Tunisia NIP recommends rubella vaccine mainly for women of childbearing age, while in Morocco, national vaccination campaigns were organized for girls and women (up to 24 years of age) to eliminate rubella. Further, travelers from both countries are recommended to follow all requirements and recommendations in the travel destination. The objective of this manuscript is to provide an overview of the global disease burden of common VPDs including (but not limited to) meningococcal diseases, pneumococcal diseases, hepatitis, and influenza. The review also provides an overview of clinical data and guidelines/recommendations on adult vaccination practices, with special focus on Tunisia and Morocco. Some European and North American countries have concrete recommendations and strategies for adult vaccination to keep the VPDs in check. In Morocco and Tunisia, although, there are sporadic adult vaccination initiatives, the efforts still need upscaling and endorsements to boost vaccination awareness and uptake. There is a need to strengthen strategies in both countries to understand the disease burden and spread awareness. Additional studies are needed to generate economic evidence to support cost-effectiveness of vaccines. Integration of private and public healthcare systems may further improve vaccination uptake in adults.